2014
DOI: 10.1371/journal.pone.0101615
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Enucleation versus Transurethral Resection in Patients with Benign Prostate Hyperplasia: An Updated Systematic Review with Meta-Analysis and Trial Sequential Analysis

Abstract: BackgroundHolmium laser enucleation (HoLEP) in surgical treatment of benign prostate hyperplasia (BPH) potentially offers advantages over transurethral resection of the prostate (TURP).MethodsPublished randomized controlled trials (RCTs) were identified from PubMed, EMBASE, Science Citation Index, and the Cochrane Library up to October 10, 2013 (updated on February 5, 2014). After methodological quality assessment and data extraction, meta-analysis was performed using STATA 12.0 and Trial Sequential Analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 34 publications
3
42
0
1
Order By: Relevance
“…Nevertheless, in a metaanalysis there were not differences found in terms of postoperative infection, although postoperative catheterization time was 5 h shorter in the HoLEP group [19]. More than 3 days postoperative catheterization could predispose to multiresistant infections [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in a metaanalysis there were not differences found in terms of postoperative infection, although postoperative catheterization time was 5 h shorter in the HoLEP group [19]. More than 3 days postoperative catheterization could predispose to multiresistant infections [20].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, these medications cannot be bridged or held due to the risk of thrombotic and embolic complications. Several series have reported on the superiority of laser enucleation and vaporization procedures over TURP to treat BPH with regard to risk of bleeding complications 2,1618. One series of 116 men undergoing PVP who continued oral aspirin, warfarin, or clopidogrel through surgery, given the risk of thromboembolic events, found no need for perioperative blood transfusions with similar decrease in postoperative hemoglobin compared to controls 19.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis by Tan et al [30] found that HoLEP showed a similar voiding efficiency and a lower complication rate than MTURP. In other recent meta-analyses, the IPSS and Qmax scores after one year among patients treated with HoLEP were slightly better than among patients treated with MTURP [3132]. However, HoLEP has the disadvantage of requiring a substantial amount of training due to the technical challenges that it poses, and it can be dangerous for unskilled surgeons to perform this procedure [7].…”
Section: Discussionmentioning
confidence: 99%